Case Report and Review of Articles: Rheumatoid Vasculitis - Salman, Sami; Yonis, Ali (Journal of the Faculty of Medicine Baghdad, 2013)
We describe here a case of a 70 yr old man with long-standing rheumatoid arthritis who presented with low grade fever, fatigue, loss of appetite and weight, bluish discoloration of the fingers and patches of gangrenous skin on the fingers. There was intense pain in the fingers which prevented him from sleep. Along with these symptoms he developed loss of sensation in the dorsum of left foot, then left foot drop. We give below full account of the case and review of the causes of vasculitis. We want to emphasize on the importance of identifying vasculitis as one of the complications of rheumatoid arthritis and intensive treatment of this complication, as it is a life-threatening complication.